Cultural potency and developing strategy of Waturaka ecotourism in Ende regency - Budiarta, I Putu; Solihin, Solihin; Sutarma, I Gusti Putu (YAYASAN MITRA PERSADA NUSANTARA, 2025)
This study aims to identify and analyze the obstacles in ecotourism practices in Waturaka Village, Kelimutu District, Ende Regency, East Nusa Tenggara Province. Waturaka Village is a buffer village for Kelimutu National Park which has great potential in developing community-based ecotourism. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and literature studies. The results of the study indicate that ecotourism practices in Waturaka Village face various obstacles, including limited infrastructure, lack of equitable community participation, minimal training and technical knowledge, and management that still requires intensive assistance. In addition, the development and promotion model that has not been maximized also hinders the advancement of ecotourism in this village. These obstacles have an impact on the sustainability of ecotourism based on conservation and empowerment of local communities. Therefore, synergy between stakeholders, increasing human resource capacity, and sustainable management strategies are needed to support the success of ecotourism in Waturaka Village.